FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH TERHADAP PRODUK RAHN PADA PEGADAIAN SYARIAH - Amanda Veronica; Muhammad Iqbal Fasa; Suharto Suharto (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
The growing development of sharia-related products that are increasingly crowded in Indonesia also has an effect on the business development of PT Pegadaian (Persero). Therefore, PT Pegadaian (Persero) also issued a new product that smelled of sharia under the name Pegadaian Syariah. The legal basis for the establishment of Sharia Pawnshops is PP No. 103 dated November 10 2000 and Fatwa DSN No. 25 / DSN-MUI / III / 2002 concerning Rahn. For this reason, this study aims to examine and analyze the effect of promotions, prices and loan disbursement procedures on customer interest in using rahn products in Islamic pawnshops. This research uses quantitative research. The type of data used in this research is primary data. Primary data is data that comes from the original source or the first one that comes from a questionnaire. Based on the analysis and data processing above, the results obtained include promotion variables that affect customer interest, price variable affects customer interest and loan disbursement procedure variables also affect customer interest. Keywords: Customer Interest, Promotion, Price / Cost, Fund Disbursement Procedure, Sharia Pawnshop